A Five-Year Study of the Efficacy of Purified CD34+ Cell Therapy for Angiitis-Induced No-Option Critical Limb Ischemia. (30th April 2018) - Fang, Yuan; Wei, Zheng; Chen, Bin; Pan, Tianyue; Gu, Shiyang; Liu, Peng; Guo, Daqiao; Xu, Xin; Jiang, Junhao; Yang, Jue; Shi, Zhenyu; Zhu, Ting; et al.
Abstract : Angiitis-induced critical limb ischemia (AICLI) patients constitute a remarkable proportion of no-option critical limb ischemia (CLI) patients. Stem cell therapy has become an innovative and promising option for no-option CLI patients. As one of these promising stem cell therapies, purified CD34+ cell transplantation (PuCeT) has shown favorable short-term results. However, the long-term efficacy of PuCeT has yet to be reported. This study evaluates the long-term efficacy of PuCeT in AICLI patients. Twenty-seven AICLI patients were enrolled from May 2009 to December 2011. Granulocyte colony-stimulating factor (G-CSF) and enoxaparin sodium were administered for 5 days. On day 5, CD34+ cell isolation was performed, and cells were transplanted by intramuscular injection. The primary endpoint, major-amputation-free survival rate (MAFS), as well as secondary endpoints, such as peak pain-free walking time (PPFWT) and the Wong-Baker FACES pain rating scale score (WFPRSS), were routinely evaluated during the 5-year follow-up period. The endpoints were as follows: the MAFS was 88.89%; PPFWT increased from 3 ± 3 to 17 ± 6 minutes; WFPRSS decreased from 7 ± 2 to 0.3 ± 1.7; the ulcer healing rate was 85.71%; the recurrence rate was 11.11%; and SF-36v2 scores were significantly improved at 5 years after PuCeT. The rate of labor recovery 5 years after PuCeT was 65.38%, and no severe adverse effect was observed during the treatment. PuCeT demonstrated long-term efficacy and durability as a treatment of AICLI not only in achieving limb salvage but also in recovering the labor competence and improving the quality of life of patients.